Dispositivos analíticos de baixo custo baseados em C4D para a determinação de macronutrientes agrícolas - Cardoso, Pedro Osmar de Almeida (Universidade Federal de São Carlos, 2021)
Agricultural activity plays a crucial role in the Brazilian socioeconomic fabric. The country, leader in several sectors of the world agribusiness, had a gigantic increase in productivity in the 20th century, largely as a result of the growing implementation of agricultural fertilizers. These inputs, however, if used incorrectly or excessively, can cause great harm to human health. Soil analyzes for the quantification of macronutrients of agricultural interest, essential for the adequacy of fertilization strategies, are traditionally expensive, time-consuming and inaccessible. Therefore, it is pertinent to use portable, inexpensive and quick-response devices to carry out such analyses. Capacitively Coupled Contactless Conductometric Detection, or C4D, is a universal, practical and versatile detection method successfully employed in the construction of these devices. The objective of this work was the use of metallic glass electrodes, constructed by cheap and accessible techniques, for the detection in C4D of the macronutrients of agricultural interest phosphate, potassium and ammonium (NPK). For the individual quantification of these ions in mixture, the complexing reagents magnesium oxide (MgO) and 18-crown-6 ether were used. Analytical curves were produced for the calibration of the electrode with each ion individually, all of which presented a linear increase in conductivity with their concentration with a coefficient of determination (R2) ≥ 0.992. Measurement quality parameters such as reproducibility (>96.0%), repeatability (>99.3%), detection limit and quantification were measured, which showed the electrode's ability to determine analytes in the order of a few μmol L–1. Several tests were carried out using combinations of NPK ions, mixed and isolated, with the complexing reagents MgO and corona. These tests, although unfinished, present optimistic perspectives, which should be further investigated for the methodological adequacy of detection. As a result, it is expected to develop a detection device of low cost and accessible production, capable of quantifying macronutrients of agricultural interest with good sensitivity, speed and practicality.
Low-cost C4D-based analytical devices for the determination of agricultural macronutrients
Keywords: NPK; Quantificação; C4D; MgO; 18-coroa-6; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO